New Chinese immigrants in Singapore : barriers of integration - Qian, Lifeng (2017)
This study explores three key propositions through analyzing how language, sentiment and policy barriers are involved in the integration process of New Chinese immigrants. Based on the empirical data gathered from them directly in addition to online news reports and forum comments, this study makes the following arguments.